The Law Application of Land Procurement for Development in Public Interest - Hendri Cahyono; Gunarto Gunarto (Sultan Agung Notary Law Review, 2021)
Implementation of the application of Article 35 of Act No. 2 of 2012 concerning Land Acquisition for the Development of Toll Roads in the Public Interest. The value of compensation based on the results of the Appraiser's assessment becomes the basis for deliberation to determine compensation. In Article 35 of Act No. 2 of 2012 it is stated that if in the case of certain land parcels that are affected by land acquisition there are remnants that can no longer be functioned according to their designation and use, the entitled Party may request a complete replacement of the parcel of land. What is meant by "no longer able to function" is a parcel of land that can no longer be used according to its original designation and use, for example a residential house that is divided so that some of it cannot be used as a residential house. The objectives of this research are as follows: 1) To examine the implementation of the application of Article 35 of Act No. 2 of 2012 concerning Land Procurement for the Development of Toll Roads in the Public Interest. 2) Knowing the problems faced in the implementation of the application of article 35 of Act No. 2 of 2012 concerning Land Procurement for the Development of the Public Interest of Toll Roads. 3) Assessing the legal impact of the implementation of article 35 of Act No. 2 of 2012 concerning Land Procurement for the Development of Toll Road Public Interest. The approach method in this writing uses a doctrinal method or what is called normative legal research and qualitative descriptive analysis, namely by aligning and describing the real situation. By answering the main problems in this journal research, namely 1) How to implement article 35 of Act No. 2 of 2012 concerning Land Acquisition for the Development of Toll Road Public Interest. 2) What are the problems faced in the implementation of article 35 of Act No. 2 of 2012 concerning Land Procurement for the Development of Toll Road Public Interest. 3) What are the legal implications of the implementation of Article 35 of Act No. 2 of 2012 concerning Land Acquisition for the Development of Toll Roads in the Public Interest.